Optimizing the Use of New Media in the Gen-Z Era to Strengthen Sustainable Tourism - Fero, David; Silalahi, Mery (Sekolah Tinggi Pariwisata AMPTA Yogyakarta, 2024)
This research aims to determine the optimization of the use of New Media in the Gen-Z era to strengthen sustainable tourism. This research method is a qualitative descriptive study. Researchers collected data through interviews and documentation. The results of this research show that Gen-Z spends around 2-3 hours per day watching and uploading videos on their various social media platforms. Through regular outreach, Gen-Z is active in spreading information and campaigns related to sustainable tourism. The content that Gen-Z likes is related to tourism and culture, short environmentally friendly videos, competitions and challenges, tourism content is quite popular with Gen-Z, this can be seen from the frequency of their use of social media. Creativity and innovation in presenting sustainable tourism content with fairly regular frequency using social media can optimize the strengthening of sustainable tourism.